Evaluation of work ability index and its association with job stress and musculoskeletal disorders among midwives during the Covid-19 pandemic - Amirmahani, Maryam; Hasheminejad, Naser; Tahernejad, Somayeh; Reza Tohidi Nik, Hamid (La Medicina del Lavoro, 2022)
Background: Musculoskeletal disorders (MSDs) and work-related stress are among the factors that can negatively affect work ability. Given the importance of midwives’ health, this study aims to evaluate the work ability of midwives and to investigate its association with the prevalence of MSDs and work-related stress in midwifery. Methods: Ninety-one midwives participated in this study. Three questionnaires, including Nordic musculoskeletal questionnaire (NMQ) plus body map, Persian version of work ability index (WAI) questionnaire, and Health and Safety Executive (HSE) job stress questionnaire, were used to collect data. Finally, the association of MSDs, work-related stress, and individual characteristics with WAI among midwives was investigated. Results: The highest rates of pain and discomfort were reported in the lower back and neck. The mean job stress was 116.08 with the highest scores on demand, role, and control subscales. The work ability among midwives was at an acceptable level of 39.07 on average. Inter-variable association analysis showed that the work ability was significantly associated with pain in the past 12 months and the number of coexisting MSDs. Job stress was not associated with work ability. Conclusions: Midwives’ WAI was at an acceptable level despite high prevalence of MSDs in midwives, the confirmation of the possible correlation between MSDs and work ability, as well as the high job stress in midwifery. Since the present study was conducted during the Covid-19 pandemic, the high stress in midwives may be partly due to the pandemic and may not be permanent. However, this level of stress may reduce the midwives’ work ability over a long time.